Visual Performance after Bilateral Implantation of a Four-Haptic Diffractive Toric Multifocal Intraocular Lens in High Myopes - John S. M. Chang; Vincent K. C. Chan; Jack C. M. Ng; Antony K. P. Law (Journal of Ophthalmology)
Background. The vision with diffractive toric multifocal intraocular lenses after cataract surgery in long eyes has not been studied previously. Objectives. To report visual performance after bilateral implantation of a diffractive toric multifocal intraocular lens in high myopes. Methods. Prospective, observational case series to include patients with axial length of ≥26 mm and corneal astigmatism of >1 dioptre who underwent bilateral AT LISA 909M implantation. Postoperative examinations included photopic and mesopic distance, intermediate, and near visual acuity; photopic contrast sensitivity; visual symptoms (0–5); satisfaction (1–5); and spectacle independence rate. Results. Twenty-eight eyes (14 patients) were included. Postoperatively, mean photopic monocular uncorrected distance, intermediate, and near visual acuities (logMAR) were 0.12±0.20 (standard deviation), 0.24±0.16, and 0.29±0.21, respectively. Corresponding binocular values were -0.01±0.14, 0.13±0.12, and 0.20±0.19, respectively. One eye (4%) had one-line loss in vision. Under mesopic condition, intermediate vision and near vision decreased significantly (all P≤0.001). Contrast sensitivity at all spatial frequencies did not improve significantly under binocular condition (all P>0.05). Median scores for halos, night glare, starbursts, and satisfaction were 0.50, 0.00, 0.00, and 4.25, respectively. Ten patients (71%) reported complete spectacle independence. Conclusions. Bilateral implantation of the intraocular lens in high myopes appeared to be safe and achieved good visual performance and high satisfaction.